Analisis Thermal Fatigue pada Nozzle Bejana Tekan Tipe Crack Gas Drier - Darmanto, Darmanto (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2013)
One of the most critical component in a pressure vessel is the nozzle because it is very sensitive to thermal fatigue. The fatigue life of a top head nozzle of crack gas drier is calculted based on ASME NBâ3216.1 module during fluctuative temperature cycle. The life of ten locations at the nozzle are caculated using two dimensions axisymmetric model. ABAQUS and ANSYS are used to analyze thermal fatigue. The life calculation result of the ten locations is infinite.Keywords: nozzle, thermal fatigue, ASME